A Cambrian fossil from the Chengjiang fauna sharing characteristics with gilled lobopodians, opabiniids and radiodonts - Liu, Jianni; Dunlop, Jason A.; Steiner, Michael; Shu, Degan (Frontiers in Earth Science, 2022)
Parvibellus atavus gen. et sp. nov. from the Early Cambrian Chengjiang fauna of China is a small fossil having a distinct cephalic region bearing a pair of lateral projections and a circular, ventral mouth. The trunk bears eleven pairs of probably flap-like appendages and a short pair of terminal projections. This character combination is unique for the Chengjiang biota. A circular ventral mouth is seen in Radiodonta and in some of the gilled lobopodians which are thought to be among the radiodont’s closest relatives. P. atavus, gilled lobopodians, opabiniids, and radiodonts also share the putative character of flap-like appendages along the trunk. However, the new fossil differs from radiodonts and gilled lobopodians by the absence of enlarged and/or raptorial frontal appendages. It also differs from gilled lobopodians by lacking in ventral lobopod limbs and from radiodonts by lacking in stalked eyes. It provisionally resolves as a sister-group to a clade containing the gilled lobopodians, opabiniids, and radiodonts, and could potentially be part of an early radiation of the nektonic lower stem—Euarthropoda.